1978
DOI: 10.1148/126.3.623
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of the Left Gastric Artery

Abstract: Five hundred celiac angiograms were reviewed to evaluate the frequency of clinically significant variations in the origin of the left gastric artery. In 13 of 500 cases, the left gastric artery arose anomalously most often as a direct branch of the aorta; in 14 of 500 cases, the left gastric artery primarily supplied the liver with only minor contributions to the stomach. An aberrant origin of the left gastric artery necessarily influences the angiographic diagnosis and therapy of gastrointestinal hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Anatomic variations of the left and right gastric arteries have often been reported [3,8]. Radiologists at our institute reported that 50 of 56 (89%) right gastric arteries were detected by CT, and that the origin of the right gastric artery was incorrectly assessed in seven cases [12].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Anatomic variations of the left and right gastric arteries have often been reported [3,8]. Radiologists at our institute reported that 50 of 56 (89%) right gastric arteries were detected by CT, and that the origin of the right gastric artery was incorrectly assessed in seven cases [12].…”
Section: Discussionmentioning
confidence: 82%
“…The replaced hepatic artery was considered important to preserve because of lethal complications of necrosis of the left lobe [6]. Naidich et al [8] reported that the left gastric artery arose as a direct branch of the aorta in 14 of 500 cases. Arising from the aorta is one of the important anomalies of vessels during lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Also variations of branches of the coeliac trunk were reported by many authors. 4 The inferior phrenic arteries are two small arteries which supply the diaphragm.…”
mentioning
confidence: 85%
“…We searched PubMed for articles using the key term “left gastric artery” published between 1946 and 2019 and found only one report on duplicate LGA. Naidich et al evaluated 500 angiograms, including at least one selective study of the celiac trunk or the gastrosplenic trunk 2 . They reported two equal caliber LGAs arising from the celiac artery in two cases (0.4%), but surgical management of patients with a duplicate LGA has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%